Effects of fine particulate matter constituents on respiratory and systemic inflammation in elderly adults with and without hypertension: A component-resolved analysis - Bo Peng; Yuanyang Liu; Yiqun Han; Wu Chen; Yifan Xu; Lia Chatzidiakou; Yunfei Fan; Li Yan; Hanbin Zhang; Benjamin Barratt; Yanwen Wang; Teng Wang; et al. (Science of The Total Environment, 2025)

Development of a concrete prototype truss structure for floating wave energy converters: Digital design, manufacture and flexural performance - Xiaoteng Li; Li Zheng; Moray Newlands; Rod Jones (Engineering Structures, 2025)

Short-term air pollution and greenness exposures on oxidative stress in urban and peri-urban residents in Beijing: A part of AIRLESS study - Wenhao Qi; Hanbin Zhang; Yiqun Han; Wu Chen; Yanbo Teng; Lia Chatzidiakou; Benjamin Barratt; Rod Jones; Frank Kelly; Tong Zhu; Junfeng Zhang; John S. Ji; et al. (Science of The Total Environment, 2024)

Determining the optimal time interval between sample acquisition and cryopreservation when processing immature testicular tissue to preserve fertility - Shiyan Tang; Celine Jones; Jill Davies; Sheila Lane; Rod T Mitchell; Kevin Coward (Cryobiology, 2024)

The Mouths of Estuaries Are Key Transition Zones that Concentrate the Ecological Effects of Predators - Tyson R. Jones; Christopher J. Henderson; Andrew D. Olds; Rod M. Connolly; Thomas A. Schlacher; Brandon J. Hourigan; Lucy A. Goodridge Gaines; Ben L. Gilby (Estuaries and Coasts, 2021)

Urbanisation and Fishing Alter the Body Size and Functional Traits of a Key Fisheries Species - Ben L. Gilby; Andrew D. Olds; Felicity E. Hardcastle; Christopher J. Henderson; Rod M. Connolly; Tyson S. H. Martin; Tyson R. Jones; Paul S. Maxwell; Thomas A. Schlacher (Estuaries and Coasts, 2020)

Clinical Predictors of Venetoclax Pharmacokinetics in Chronic Lymphocytic Leukemia and Non-Hodgkin’s Lymphoma Patients: a Pooled Population Pharmacokinetic Analysis - Aksana K. Jones; Kevin J. Freise; Suresh K. Agarwal; Rod A. Humerickhouse; Shekman L. Wong; Ahmed Hamed Salem (The AAPS Journal, 2016)

The influence of stem guying on radial growth, stem form and internal resin features in radiata pine - John R. Moore; David J. Cown; John R. Lee; Russell B. McKinley; Rod K. Brownlie; Trevor G. Jones; Geoffrey M. Downes (Trees, 2014)

Application of a coastal model to simulate present and future inundation and aid coastal management - Peter E. Robins; Alan G. Davies; Rod Jones (Journal of Coastal Conservation, 2011)

A framework for the management of sand dune systems in Wales - Peter Rhind; Rod Jones (Journal of Coastal Conservation, 2009)

Evidence that orexin-A-evoked grooming in the rat is mediated by orexin-1 (OX 1 ) receptors, with downstream 5-HT 2C receptor involvement - Mark S. Duxon; Jennifer Stretton; Kathryn Starr; Declan N.C. Jones; Vicky Holland; Graham Riley; Jeff Jerman; Stephen Brough; Darren Smart; Amanda Johns; Wai Chan; Rod A. Porter; et al. (Psychopharmacology, 2001)

Effects of centrally administered orexin-B and orexin-A: a role for orexin-1 receptors in orexin-B-induced hyperactivity - Declan N.C. Jones; Jane Gartlon; Frederick Parker; Stephen G. Taylor; Carol Routledge; Panida Hemmati; Richard P. Munton; Tracey E. Ashmeade; Jonathan P. Hatcher; Amanda Johns; Rod A. Porter; Jim J. Hagan; et al. (Psychopharmacology, 2001)

Transitions between Auhcoseira and Anabaena dominance in a turbid river weir pool - Bradford S. Sherman; Ian T. Webster; Gary J. Jones; Rod L. Oliver (Limnology and Oceanography, 1998)
The transitions between the diatoms Aulacoseira spp. ( Melosira ) and the cyanobacteria Anabaena spp. as dominant phytoplankton species in a turbid‐river weir pool are shown to depend directly on the establishment or destruction of persistent thermal stratification. A transition from high to low flow through the pool resulted in the establishment of persistent thermal stratification, causing Aulacoseira to sink out of the euphotic zone at a speed of 0.95 m d −1 . Concurrently, the slightly buoyant Anabaena grew within the euphotic zone with a specific growth rate of 0.37 d −1 , climaxing after approximately 14 d at a population of 20,000–30,000 cells ml −1 , at which point its biomass may have been limited by the availability of phosphorus. The stratification thus caused the phytoplankton population to separate into two distinct layers, with Anabaena occupying the illuminated surface layer and Aulacoseira found only in the lower layer below the euphotic depth. Under stratified conditions, the ratio of the surface layer depth to euphotic depth, z sl : z eu , was approximately 1, whereas for a mixed water column that ratio was >3. Access to light appeared to be the main factor determining the dominant phytoplankton species.